Impact of Intraaortic Therapy on Metabolic Changes in Patients with Peritoneal Sepsis Complicated by Multiple Organ Dysfunction - A. Yu. Yakovlev; G. A. Boyarinov; I. V. Mukhina; Ye. V. Dudina (Общая реаниматология, 2005)
The study was undertaken to analyze the parameters of metabolism and lipid peroxidation when intraaortic infusion therapy was used in combination with sodium hypochlorite. The time course of changes in lactate and glucose levels, appropriate indices, LPO/AOS parameters shows the preference of a complex of intraaortic therapy in the volume of 50—60 ml/kg/day and daily intraaortic injection of 400—500 ml of 0.06% sodium hypochlorite solution and 800 ml of reamberin to other modes of intraaortic correction of metabolic disturbances.